Contractual law of Ukraine: present state and the development trends - Луць, Володимир Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
This article is devoted to the research of contract institute development and trends of civil and contract legislation development. An author analyses the provisions of the Civil and Economic Codes and other legislative acts of Ukraine in the process of contractual relations regulation.